Effect of mental imagery training on novice archery athlete performance / Muhammad Rafiudin Sa'ari - Sa'ari, Muhammad Rafiudin (Faculty of Sport Science and Recreation, 2018)
Imagery has been shown to be one of most effective psychological tool in enhancing athlete performance in a variety of sports. The main purpose of this study was to identify the effect of mental imagery training on novice archery athlete performance with additional purpose to compare differences between novice and expert athlete shooting accuracy performance. The intervention cross-sectional research design was used in this study which involved pre and post-test with treatment intervention. Subjects were 12 archery athletes employed from Majlis Sukan Negara (Pahang) with an average age of 15.8 years old (sd=l.03). Subjects were divided into two groups: novice athlete (experimental group), expert athlete (control group). Pre and post-test with treatment·, intervention design was implemented in this study. A set of data was recorded: shooting accuracy. It was found that novice athlete improved between pre-test (M=72.83, sd=9.80) and post-test (M=79.83, sd=7.80). This study also found that there are differences between novice and expert athlete shooting accuracy performance with expert athlete scored M=91.83 (sd=3.76) on pre-test compare to M=72.83 (sd=9.80) for novice athlete while in post-test, expert athlete scored M=94.50 (sd=1.87) compared to novice athlete, M=79.83 (sd=7.80). Implications from this study might provide beneficial training method for novice archers to increase their shooting accuracy performance.